Guest Editors' Introduction to Special Issue: Bush Lessons Down Under - Geoff Danaher; Beverley Moriarty; Patrick Alan Danaher (Journal of Research in Rural Education, 2003)
One of the consequences of living in an increasingly globalized and internationalized world is that there are often striking similarities"at least superficially"in how particular educational (and also cultural, economic, political, social, and technological) phenomena are manifested in countries (certainly in developed nations) around the globe. At the same time, these similarities should not blind researchers to the heterogeneous variations on local manifestations of global phenomena.